Change in Marijuana Use and Related Problems among Adolescents in Substance Use Disorder Treatment: The Mediating Effects of Alcohol Consumption. Issue 5 (8th August 2019) - Spinola, Suzanne; Moskal, Dezarie; Maisto, Stephen A.; Park, Aesoon; Labbe, Allison K.; Chung, Tammy A.
Abstract: As the number of adolescents seeking treatment for marijuana use increases, it is important to identify factors that mediate marijuana treatment outcomes. Alcohol consumption is highly prevalent in clinical samples of adolescents but has been neglected as a potential mediator of marijuana use treatment outcomes. In this study, we sought to examine alcohol consumption as a mediator of both marijuana use frequency (number of use days) and negative consequences related to marijuana use in a longitudinal study of 159 adolescents ( M age = 16.69 years; 35% female; 87% White; 70% marijuana as a preferred drug) enrolled in intensive outpatient substance use disorder (SUD) treatment. It was hypothesized that change in both frequency and quantity of alcohol consumption from baseline to 6-month follow-up mediates the association between marijuana use frequency and marijuana-related problems at baseline and 12-month follow-up. Results of path analyses showed that the number of drinking days and total number of drinks consumed at 6 months significantly mediated the change in marijuana-related problems over 12 months, after controlling for gender, preferred drug, and pre-treatment alcohol consumption. However, alcohol consumption was not found to mediate the change in marijuana use frequency. These results highlight the importance of examining both use- and non-use-based treatment outcomes to obtain a more complete picture of treatment outcomes. The findings also suggest that researchers and clinicians should address the use of multiple substances in an integrated way, rather than focusing primarily on an individual's preferred drug.